BCC-superalloys: Perspectives and challenges - Knowles, Alexander J.; Zenk, Christopher (Scripta Materialia, 2025)
Body-centred-cubic BCC-superalloys are a nascent materials class following a microstructure template of a disordered BCC matrix (e.g. refractory metal, Fe, Ti) reinforced by coherent precipitates that adopt a BCC-derived ordered superlattice structure, to enable enhanced high temperature performance. This is by analogy to the highly successful Ni superalloys whose properties are underpinned by their microstructure template of γ/γ′ FCC-Ni solid solution and ordered Ni3Al. BCC-superalloys represent a powerful Beyond Nickel Based Superalloy design approach for high temperature applications from aerospace engines and rockets to fusion energy. Various BCC-superalloy base systems offer increased melting points, oxidation/corrosion/irradiation resistance, reduced density and/or cost advantages. However, challenges exist in phase stability, low temperature ductility, oxidation/corrosion resistance and the availability of predictive tools. This BCC-superalloys Viewpoint Set addresses key challenges, theories and opportunities across the following overarching topics: Modelling, Phase transformations, Lattice misfit, Mechanical behaviour, Deformation mechanisms, Oxidation/corrosion, and Additive manufacturing.
CRIS-Team Scopus Importer:2025-07-04
Keywords: Alloy design; BCC-superalloys; Environmental resistance; Mechanical behaviour; Microstructure